Nilai-Nilai dalam Pertimbangan Seriousness Of Crime: Kajian Pada Komunitas Muslim - Fathul Lubabin Nuqul (Faculty of Sharia and Law - Sunan Kalijaga State Islamic University, 2011)
Public opinion about seriousness of crime was influenced by much internal from person (observer) variable, beside variable form nature of crime and criminal profile. One of internal variable is value which in embracing by individual, one of the values is coming from religion value. In religion values, especially Islamic value, arranges people behavior in relating with his god and with other people. This religion value also influences their opnion to crime and action as response to crime. Nevertheless has not many field studies yet publication explaining about the Islam value in criminal justice system phenomenon and influence at people behavior, so that it generates many questions about how Muslims opinion crime and criminal justice system. The purpose of the research is to know crimes was assumed is serious for Muslim and Muslims consideration are in determining seriousness of crime. There search involves 163 psychology undergraduate. In the research, respondent asked to choose out of 23 form of crime assumed most serious and followed with open-end questionnaire related to reason of election of crime that is most serious. The result shows that apostates (murtad), intended genocide and corruption are most serious crime. Goodness and humanity value is most dominant reason in determination of seriousness of crime. Opinion about seriousness crime has implication at assessment of justice at Law enforcement.